AGROBISNIS SEKTOR PETERNAKAN AYAM BROILER - -, Astuti (INOTEKS: Jurnal Inovasi Ilmu Pengetahuan,Teknologi, dan Seni, 2005)
Problems of educated (university graduates) unemployed people should be solved 1;-:e irel-waste man powers. An effort to reform the graduates, therefore they can help r:=selves by creating their own jobs was conducted. The university gave some expertise –;:::-r entrepreneur attitudes and skills through a program calles "Magang :r.:t i:ausahaan (MKU)" -rr Such a program presented in Biology Departement, FMIPA LINY, was an in- ice training on business of boiler raising. The participants were ten selected studens :: Semester VIIL Selection was based on their interest in running business of broiler ::,ising. The selected students were then given some knowledge in business management, ::oposing new business, composing chicken diet, and techniques in raising broiler. The ibilorving step was then sending the students to the link industry. The link industry located in Wonosalam, Ngemplak, Sleman. During the training st’;dents worked any kind clf scheduled jobs shiftingly under supervision of business o er. The lecturer team visited regularly once a week. It was expected that all students could do any kind of job related to raising broiler. and the entrepreneur attitudes could der,elop due to their involvement in business. It was a good point for the students that the business owner was very supportive to this and the following program. In order to evaluate students understanding and involvement in the business, they were required to present a business proposal in broiler raising. On the basis of the success of this program, Departement of Biology IiMIPA LINY encourages to develop programs of laboratory practice and field work which have entreprenuer perspective in order to integrate the entrepreneurship to the existed curruculum